Prepare food systems for a long-haul fight against COVID-19 - Torero, Maximo (International Food Policy Research Institute, 2020)
With a devasting one-two punch, a supply shock followed by a demand shock, the COVID-19 pandemic has knocked out the world economy. The first blow was the Great Lockdown; the second, the worst recession since the Great Depression. No modern economy has experienced anything like this. As the spread of the novel coronavirus debilitates people’s ability to harvest and buy and sell food, food systems are under threat as never before.